2020
DOI: 10.1007/s00216-020-02939-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical multi-analyte point-of-care perspiration sensors using on-chip three-dimensional graphene electrodes

Abstract: Multi-analyte sensing using exclusively laser-induced graphene (LIG)-based planar electrode systems was developed for sweat analysis. LIG provides 3D structures of graphene, can be manufactured easier than any other carbon electrode also on large scale, and in form of electrodes: hence, it is predestinated for affordable, wearable point-of-care sensors. Here, it is demonstrated that LIG facilitates all three electrochemical sensing strategies (voltammetry, potentiometry, impedance) in a multi-analyte system fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 55 publications
(72 reference statements)
0
42
0
Order By: Relevance
“…Laser-induced graphene was studied as an alternative, carbonaceous material for electrochemical (bio)sensing applications. Its promising characteristics described by us earlier [15,16] indicate that it may be not only an alternative but a superior transducer material for electrochemical point-of-care sensors. Not much is known about the effect of energy input during the fabrication in correlation to electroanalytical performance, only anecdotal data are available describing obtainable micromorphologies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser-induced graphene was studied as an alternative, carbonaceous material for electrochemical (bio)sensing applications. Its promising characteristics described by us earlier [15,16] indicate that it may be not only an alternative but a superior transducer material for electrochemical point-of-care sensors. Not much is known about the effect of energy input during the fabrication in correlation to electroanalytical performance, only anecdotal data are available describing obtainable micromorphologies.…”
Section: Resultsmentioning
confidence: 99%
“…Fenzl et al used pyrenebutyric acid to couple a thrombin aptamer to the LIG matrix and demonstrated that it can be successfully used in an aptasensor [15]. Also, recent work from our lab describes a combination of amperometry-, potentiometry-, and impedance-based sensors made from LIG for the measurement of lactate, potassium, and conductivity in sweat [16]. Other groups have modified DLW-created carbon electrodes with copper nanoparticles alone or in combination with diamine oxidase to detect glucose or biogenic amines respectively [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology could offer a possible path for development of precise and accurate sensors by facilitating design of novel materials and enabling selective surface modification. In recent years, materials like graphite, graphene (Shahdeo et al 2020 ; Bauer et al 2021 ), carbon nanotubes (Sobhan et al 2020 ), and chitosan (Lin et al 2020 ) have shown promising results for the development of lab-on-a-chip devices and their scale-up. Further, scale-out strategies must also be explored to achieve higher throughput in production.…”
Section: Challengesmentioning
confidence: 99%
“…As concerns the enzymatic biosensors, LIG modified with electrodeposited Pt NPs was explored to detect glucose by the amperometric response when H 2 O 2 , as a by-product of the enzymatic reaction, is oxidized by the Pt NPs [ 16 , 17 ]. Another example relies on the immobilization of Prussian blue, as electron mediator, on LIG electrodes to detect glucose oxidation by the enzyme [ 18 ]. LIG was also explored for the detection of the biomarkers AA, UA and DA [ 4 , 19 , 20 ], and for the sensing of thrombin [ 21 ] and urea [ 22 ] using specific biorecognition elements.…”
Section: Introductionmentioning
confidence: 99%